Pendidikan Kitab Suci Al-Qur’an: (Studi Analisis Buku Anthology of World Scriptures Karya Robert E. Van Voorst) - Rafiudin (Adz-Zikr : Jurnal Pendidikan Agama Islam, 2019)
Education is one of the tools of humanity in understanding themselves and their environment. The higher the value of the facilities used, the higher the quality of education obtained by humans. The Holy Qur'an has the highest authority in the eyes of Muslims compared to any book on the face of the earth. So the education based on the holy book of the Qur'an gives birth to the best quality. The highest authority of the Qur'an in developing education is found in several conclusions, namely the Qur'an as a revelation passed down through the intermediary angel Gabriel to the prophet Muhammad, as a revelation of many miracles contained in the Qur'an, among others, reported with faith and the Islamic language of a person is also a very noble language because there is not a single creature that can match its perfection, the content of the Qur'an which is used as a refinement of all previous books and then makes it as the most trusted guide book, and the Qur'an has a value as holy books that contain signs of technological progress in all fields.